Use of a dynamic absorber in the case of a vibrating printed circuit board of complicated boundary shape - la Malfa, Salvador (2000)
An experimental investigation was carried out to examine the feasibility of using a dynamic absorber when a printed circuit board (PCB) of complicated boundary shape operates under resonance conditions. The dynamic response of the hexagonal plate was observed before placing the dynamic absorber and once the tuning operation was performed. As expected: the plate velocity amplitude experienced a highly noticeable decrement: from 4.697 to 0.7367mm/s.